Semiotics Analysis of COVID-19 Vaccine Photos in Wasapada Newspaper - Harahap, Muhammad Said; Khadafi, Rizal; Hasibuan, Effiati Juliana (Jurnal Ilmu Komunikasi, 2024)
In the current digital era, mass media play a crucial role in assisting the government in overcoming the COVID-19 pandemic. The responsibilities of this position encompass the dissemination of information pertaining to appeals, recommendations, news, and socialization efforts regarding government policies pertaining to the COVID-19 pandemic. The objective of this study is toexamine the optimization of COVID-19 mitigation efforts through the dissemination of mass vaccine photo news in HarianWaspada, a newspaper in the North Sumatra Province of Indonesia. The analysis of the photograph depicting mass vaccination wasconducted employing the semiotic approach in order to examine the denotative, connotative, and mythological implicationsembedded within the image. The interview method was employed to gather insights from photographers and editors affiliated with Harian Waspada who were actively engaged in the coverage of mass vaccine-related news. The findings of this study demonstrate that Harian Waspada, in addition to its commitment to disseminating knowledge to the wider community through photo news. The inclusion of mass immunization photos in news articles serves as an engaging element for readers. The inclusion of human-interest photographs in Harian Waspada, depicting mass vaccination efforts, serves the purpose of evoking emotionssuch as wonder, pity, joy, or despair.